Employee engagement for dummies - Kelleher, Bob. (John Wiley & Sons, 2014)
Today more than ever, companies and leaders need a road map to help them boost employee engagement levels. Employee Engagement For Dummies helps employers implement the necessary plans to create and sustain an engaging culture, allowing them to attract and retain the best people while boosting their productivity and creativity.